Provider Perspectives on Persistent Urinary Incontinence Following Obstetric Fistula Repair in Ethiopia - Jacobson, Laura E.; Marye, Melaku Abriha; Phoutrides, Elena; Nardos, Rahel (Frontiers in Global Women's Health, 2020)
Each year an estimated 50,000 to 100,000 women worldwide are affected by obstetric fistula. This devastating but preventable maternal morbidity leaves women incontinent, stigmatized, isolated, and often with a still birth. While fistula rates in Ethiopia have declined in recent years, estimates range from 7-40 percent of women suffer from persistent urinary incontinence after successful closure of their fistula. Few studies have focused on the unique experiences and challenges that providers face treating fistula patients, particularly those who experience persistent urinary incontinence. The goal of this research is to characterize the fistula provider’s accounts of how to manage, support, and understand their patient’s experience. Semi-structured interviews were conducted with a purposive sample of fistula care providers in Mekelle and Addis Ababa, Ethiopia. The main themes that emerged were a perceived exacerbated impact on quality of life for women with persistent urinary incontinence; a "double hit" of isolation from both their community and from other recovered fistula patients; how the church both influences how patients internalize their injury and provides them with hope and support; and the need for comprehensive and compassionate fistula care. Understanding how providers perceive and relate to their patients provides valuable insight to the unique challenges of treating this population and may better inform treatment programs to address the gap between patient needs and current fistula care models.